Dual-targeted STAb-T cells secreting BCMA and CD19 T cell engagers for improved control of haematological cancers - Miriam Velasco-Sidro; Javier Arroyo-Ródenas; Laura Díez-Alonso; Ángel Ramírez-Fernández; Luis Álvarez-Vallina (OncoImmunology)
Despite recent advances in immunotherapy against B cell malignancies such as BCMA (B cell maturation antigen) and CD19-targeted treatments using soluble T cell-engaging (TCE) antibodies or chimeric antigen receptor T cells (CAR-T), there is still an important number of patients experiencing refractory/relapsed (R/R) disease. Approaches to avoid tumor-intrinsic mechanisms of resistance such as immune pressure-mediated antigen downmodulation, are being broadly investigated. These strategies include BCMA/CD19 dual-targeting therapies, which may be of particular interest to patients with B cell lymphoma and multiple myeloma, where a specific double-positive immature subpopulation is commonly associated with poor prognosis and poor response to current treatments. In fact, several clinical trials targeting both antigens through different strategies are currently underway. Here, based on the previously validated STAb (in situ secretion of T cell-redirecting bispecific antibodies) concept, we used two different engineering strategies (pool and co-transduction) to generate dual-targeted STAb-T cells simultaneously secreting BCMA TCE and CD19 TCE that outperformed single-targeted STAb-T cells in different in vitro models. These promising results encourage further preclinical clinical testing of dual STAb-T cells in R/R B-cell malignancies.